2022
DOI: 10.1021/acs.macromol.2c00894
|View full text |Cite
|
Sign up to set email alerts
|

Colorless Polyimides from Fluorinated Ladder Diamines Containing Norbornyl Benzocyclobutene Segments

Abstract: Three fluorinated ladder diamines with norbornyl benzocyclobutene (N2BC) segments were prepared by catalytic norbornene-arene annulation (CANAL) reactions of norbornadiene with fluorinated bromoanilines. NMR results revealed that two regioisomers were obtained for each diamine, with syn-to-anti ratios of ∼2:1. High-temperature solution polycondensation of these diamines with commercial dianhydrides produced a series of colorless polyimides (CPIs). These polymers exhibited extremely high glass-transition temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Huang 22 introduced perfluorocyclobutyl aryl ether groups into polyimide with D k (2.37–2.78) and D f (0.0035–0.0071) and guessed that the lower dipole moment density was the main factor in reducing the dielectric loss. However, Wang 23 synthesized low dipole polyimides with fluorinated ladder diamines with low D k (2.59–3.35) and D f (0.004–0.025), indicating that polyimides with low dipoles may also have higher D f . Therefore, it seems that dipoles are not the main cause of high D f .…”
Section: Introductionmentioning
confidence: 99%
“…Huang 22 introduced perfluorocyclobutyl aryl ether groups into polyimide with D k (2.37–2.78) and D f (0.0035–0.0071) and guessed that the lower dipole moment density was the main factor in reducing the dielectric loss. However, Wang 23 synthesized low dipole polyimides with fluorinated ladder diamines with low D k (2.59–3.35) and D f (0.004–0.025), indicating that polyimides with low dipoles may also have higher D f . Therefore, it seems that dipoles are not the main cause of high D f .…”
Section: Introductionmentioning
confidence: 99%
“…That is, it should appear in the top right corner of Figure b. Compared with recent reports, the comprehensive performance of CPI-PA 4 obtained in this work is outstanding. , , The strategy of PA by in situ polymerization in CPI has significant advantages in improving the dimensional stability and thermal properties while maintaining the optical transparency of CPI films …”
Section: Resultsmentioning
confidence: 63%
“…[28] For example, Liu et al [29] reported the PI from 1,2,4,5-cyclohexane-tetracarboxylic dianhydride (CHDA) and triphenylmethylene diamine showed moderate T d5 of 473 °C. The T d5 s of PIs from CpODA and ladder diamines [30] are generally below 480 °C.…”
Section: Introductionmentioning
confidence: 99%